DETERMINAN HASIL BELAJAR ANAK: LINGKUNGAN KELUARGA, LINGKUNGAN SEKOLAH, DAN LINGKUNGAN MASYARAKAT - Manullang, Tetti; Silitonga, Mirdat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The success of education is determined by the ability of various parties to understand and achieve educational goals. This study aims to analyze the determinants of learning outcomes. The research method used is the survey method. Survey research method is used to provide an overview of what factors determine children's learning outcomes. The sampling technique used in this research is proportional random sampling. The sample of this study was all students of class X, totaling 71 people. Sample is part of the number and characteristics possessed by the population. The sample that will be taken from the affordable population is based on the table of determining the number of samples from Issac and Michael with an error rate of 5% as many as 57 students. The data analysis technique used in this study uses quantitative methods, to get the results of which determination factor is the highest. The results of the study found that the correlation coefficient of the family environment with learning outcomes was 0.444 (p≤ 0.01) while the determinant coefficient is 19.71 percent. Which means that children's learning outcomes are determined by the family environment by 19.71 percent. The correlation coefficient between the community environment and learning outcomes is 0.324 (p≤ 0.05) while the determinant coefficient is 10.49 percent. Which means that children's learning outcomes are determined by the community environment by 10.49 percent. The largest correlation coefficient is the school environment, which is 0.520 (p≤ 0.01) with a determinant coefficient of 27.04 percent. Which means that children's learning outcomes are determined by the community environment by 27.04 percent. The results of this study found that the highest determinant of learning outcomes was the school environment. To achieve good children's learning outcomes, support from various parties is needed, especially the environment closest to the child, namely the school environment and family environment. The school and parents must work together to achieve good learning outcomes for children.